Reassessing and refining theory in qualitative accounting research: an illustrative account of theorizing - Taylor, Lynda C. (Emerald, 2018)
Purpose: This paper focuses on the role of theory in the process of doing qualitative research. It seeks to show how theory was reflected upon, reassessed and refined during the research process. In so doing, it provides an illustrative account of theorizing in qualitative research, with specific emphasis on an abductive approach to theorizing. Design/methodology/approach: This paper is based on a qualitative accounting case study in which an initial theoretical framework was reassessed and refined during the research process. The approach is to reflect on the use of theory during the research process rather than on the organization itself. Findings: The ‘findings’ reflect on the use of theory and the process of theorizing during a research process. The paper finds that abduction may be a useful way of theorizing in qualitative accounting research because it encourages the researcher to remain open to alternative explanations of data, which may promote theoretical development. As such, this paper does not report the accounting practices of an organization in the traditional sense, but does so in a way that illustrates how the empirical findings led to an initial theoretical framework being developed. Practical implications: The paper is intended to be informative in showing how theory can be used and developed during research. It may be of value and interest to new and emerging researchers. It may also interest established researchers seeking to reflect on their use of theory in research. Originality/value: There are few contributions that focus exclusively and explicitly on how theory is used and developed during the process of qualitative accounting research. Moreover, the abductive approach has received limited attention in accounting. This paper aims to address these gaps.